Atlas of toxicological pathology - Gopinath, Chirukandath (Humana Press, 2014)
This atlas contains more than 700 illustrations that the authors have collected over the years as well as references and information pertaining to recently developed drug classes, including biologics. It is a useful bench reference for practicing pathologists and may also be used as a reference text by other experts from related fields. The atlas is organised into different chapters based on systemic pathology. Each chapter has illustrations with legends, and the atlas includes some rare examples of unique lesions found during toxicity studies over many years.